Relationship Between Self-Control and Internet Addiction During The Covid-19 Pandemic in Class XI Students At 99 Jakarta Public High School Even Semester in Academic Year 2021/2022 and Its Review From an Islamic View - Ratu Rohmah Januba; Sri Hastuti Andayani; Firman Arifandi (Junior Medical Journal, 2022)
Background: Circular Letter Number 4 of 2020 issued by the Ministry of Education and Culture (Kemendikbud) concerns the existence of educational platforms in an emergency situation of the spread of COVID 19 as well as instructions regarding the learning system from home. There have been changes in learning in schools that have turned online, the use of gadgets excessive and not necessarily will lead to internet addiction. The impact of internet addiction is that it can increase the intensity of teenagers to play the internet. The purpose of this study focuses on the relationship between self-control and internet addiction during the COVID-19 pandemic in class XI students at SMA Negeri 99 Jakarta in the even semester of the 2021/2022 academic year from an Islamic viewpoint.Methodes: this study uses an observational study with a cross-sectional approach to see the relationship between self-control and internet addiction during the COVID-19 pandemic in class XI students at SMA Negeri 99 Jakarta, even semester of the 2021/2022 academic year.Result: The results of the analysis of the relationship between self-control and internet addiction show a correlation coefficient (r) = -0.514 and a significance value of 0.000 (p 0.05), it can be concluded that self-control has a significant effect on internet addiction. Thus, there is a negative relationship between the two variables, where the lower the self-control, the higher the level of internet addiction. The results of this study indicate that 146 respondents (45.6%) experienced mild addiction, 90 respondents (28.1%) experienced moderate addiction, and 83 respondents (25.9%) were not addicted.Conclusion: It can be seen that most respondents experienced mild addiction. This shows that the tendency of internet addiction in the online learning process in class XI students of SMA Negeri 99 Jakarta in the even semester of the 2021/2022 academic year is in the moderate category, so it can be said that self-control in using the internet can stop habits or control oneself well to access the internet.